School-Based Management: Improving the Quality of Guidance and Counseling Services in Islamic SMK. - Rosidi, Ayep; Khuriyah, Khuriyah (At-Tarbiyat, 2024)
This study examines the implementation of school-based management (SBM) in improving the quality of guidance and counseling services at SMK Islam Sudirman 1 Ambarawa. The method used in this research is a qualitative approach with interview, observation, and document analysis techniques. The results showed that SBM provides greater autonomy to educational institutions, enabling more effective resource management and increased participation of school and community members in achieving national education goals. The implementation of SBM requires close cooperation between all stakeholders, including principals, teachers, students, counsellors, as well as government representatives and educational organizations. Therefore, the preparation of the guidance and counseling program must involve the active participation of all stakeholders and uphold the principle of openness. This research emphasizes the importance of collaboration in improving the effectiveness of guidance and counseling services at SMK Islam Sudirman 1 Ambarawa. The impact of this research on the science of Islamic education is an increased understanding of effective management practices and the relevance of guidance and counseling in supporting holistic student development.